Satellite-based rice monitoring system in India and the Philippines - CGIAR Research Program on Rice (2018)
The system was completely handed over to the Philippine Department of Agriculture through the Philippine Rice Research Institute (PhilRice) who now fully operates PRISM. The system is used operationally for crop insurance support in Tamil Nadu and Andhra Pradesh, India.